Pergumulan Iman Lanjut Usia Jemaat HKI Partangga Pasca Gempa di Tapanuli Utara, 01 Oktober 2022 Berdasarkan Perspektif Teologi Bencana - Merlin Asima Hutagaol; May Rauli Simamora; Junjungan Simorangkir; Warseto Freddy Sihombing (Jurnal Magistra, 2024)
This study aims to determine how the elderly congregation responded to the earthquake disaster, and the faith struggles of the elderly of the HKI Partangga church congregation after the earthquake based on the perspective of disaster theology. The theory used in this study is to use expert theories related to disaster theology, the theory of Zakaria J. Ngelow which emphasizes that natural disasters occur not as punishment from God, but as normal events in nature and there is no biblical record that says that God punishes sinful humans, but loves and forgives, redeems and saves humans from the wrapping of sin. The study in this research uses a qualitative method, with a descriptive analysis approach, which aims to describe the actual situation. Data collection techniques are carried out by observation, in-depth interviews. The findings of this study are that the elderly of the HKI Partangga congregation responded to the earthquake with: the emergence of fear, feeling the presence of God. In addition to responding, the elderly also provide perspectives that are different from the perspective of disaster theology on natural disasters. The elderly provide a perspective that is different from the Christian faith, which understands that earthquakes are God's punishment for sin, questions arise to God about what sins are committed, earthquakes are God's plan.